Desiccation and supra‐zero temperature storage of cat germinal vesicles lead to less structural damage and similar epigenetic alterations compared to cryopreservation. Issue 12 (23rd September 2019) - Lee, Pei‐Chih; Comizzoli, Pierre
Abstract: Understanding cellular and molecular damages in oocytes during exposure to extreme conditions is essential to optimize long‐term fertility preservation approaches. Using the domestic cat ( Felis catus ) model, we are developing drying techniques for oocytes' germinal vesicles (GVs) as a more economical alternative to cryopreservation. The objective of the study was to characterize the influence of desiccation on nuclear envelope conformation, chromatin configuration, and the relative fluorescent intensities of histone H3 trimethylation at lysine 4 (H3K4me3) and at lysine 9 (H3K9me3) compared to vitrification. Results showed that higher proportions of dried/rehydrated GVs maintained normal nuclear envelope conformation and chromatin configuration than vitrified/warmed counterparts. Both preservation methods had a similar influence on epigenetic patterns, lowering H3K4me3 intensity to under 40% while maintaining H3K9me3 levels. Further analysis revealed that the decrease of H3K4me3 intensity mainly occurred during microwave dehydration and subsequent rehydration, whereas sample processing (permeabilization and trehalose exposure) or storage did not significantly affect the epigenetic marker. Moreover, rehydration either directly or stepwise with trehalose solutions did not influence the outcome. This is the first report demonstrating that the incidence of GV damages is lower after desiccation/rehydration than vitrification/warming. Abstract : This study explored structural and epigenetic damages in germinal vesicles during exposure to extreme conditions. Results demonstrated that desiccation/rehydration affected the similar epigenetic pattern and provided better protection to nuclear envelope (NE) conformation and chromatin configuration than vitrification/warming.